Antenatal, Perinatal and Neonatal Factors Associated with Periventricular White Matter Injury in Very Preterm Infants. (1st June 2016) - Ghotra, S; Vincer, M; Allen, V; Khan, N; Kuhle, S
Abstract: BACKGROUND: Although survival outcome in preterm infants has reached nearly 90%, long-term motor and cognitive disability and cerebral palsy in survivors remain an important concern. Periventricular white matter injury (WMI) is the major form of brain injury underlying these neurological morbidities. Cystic periventricular leukomalacia (cPVL) and porencephaly contribute significantly to poor long-term neurodevelopmen-tal outcomes. Currently, there is no definitive therapy available to treat cPVL or porencephaly. The management mainly lies in identification of associated risk factors and their prevention. Most studies on risk factors of cPVL are limited in their retrospective case-control design and sample size, and have an inherent selection bias with the use of hospital-based data. OBJECTIVES: To identify risk factors for cPVL and porencephaly in a population-based cohort of very preterm infants. DESIGN/METHODS: A retrospective population-based cohort study was conducted at the at the IWK Health Centre, Halifax, Nova Scotia, using data derived from the provincial Perinatal Follow-Up Program (PFUP) database. The PFUP database contains patient data for all pre-term infants born at a gestational age (GA) of <31 weeks in Nova Scotia since 1993. Infants born at 22 to 30 weeks from 1993 to 2013 (21 years) were included in the study. Infants with severe congenital malformations or chromosomal anomalies or who died in the first 6 weeks of life were excluded. Information on potential risk factors (divided into 3 groups: antenatal, perinatal and neonatal) as well as the presence or absence of cPVL and porencephaly diagnosed by cranial ultrasound at 6 weeks of age were extracted. Variables with a P value of < 0.20 in the univariate analysis were entered in the multivariate model using a backwards selection procedure. RESULTS: Of 1184 infants found eligible for the study, 87 (7.4%) had cPVL or porencephaly. Mean GA and birth weight were 27.9 weeks and 1133 g, respectively. The gestational age-adjusted prevalence of cPVL or porencephaly did not decrease over time (p=0.07). In multivariable logistic regression analysis, chorioamniotis (OR 2.2, 95% CI 1.1-4.3), antenatal steroids (OR 0.33, 95% CI 0.18-0.61), admission hypothermia (OR 1.8, 95% CI 1.1-2.9), ventilator support (OR 4.8, 95% CI 1.4-16.9), and non-coagulase negative staphylococcal (OR 2.4, 95% CI 1.2-4.9) and fungal (OR 5.2, 95% CI 1.4-18.6) infections were independently associated with cPVL or porencephaly in the final model. CONCLUSION: This population-based cohort study has identified a number of clinically relevant factors associated with cPVL or porenceph-aly in very preterm infants. The findings have important implications in the delivery of perinatal and neonatal care to reduce the incidence of WMI and consequent, neurological morbidity.